Spinopelvic Dissociation: A Retrospective Case Study and Review of Treatment Controversies. Issue 14 (15th July 2018) - Chou, Daud Tai Shan; El-Daly, Ibraheim; Ranganathan, Arun; Montgomery, Alexander; Culpan, Paul; Bates, Peter
Abstract : Introduction: Spinopelvic dissociation is a rare injury resulting in discontinuity between the spine and pelvis. We review the English- language literature and discuss critical treatment controversies. We present a series of spinopelvic dissociation cases from a level I trauma center. Methods: In this retrospective review of 18 consecutive cases treated surgically over a period of 4 years, we collected patient, injury, and surgical demographics and clinical and radiographic outcome measures. Results: Twelve patients had associated injuries, five were intubated on arrival, and six had neurologic deficits at presentation. No patient had spinal decompression, and all patients underwent closed reduction and percutaneous fixation. There were no cases of iatrogenic nerve injury, despite the use of partially threaded sacroiliac screws and closed reduction techniques. Five patients showed progressive neurologic improvement postoperatively. After reduction, eight patients (44%) had radiographic loss of the sacrococcygeal angle at the latest follow-up, but correction of fracture translation was preserved in all. Discussion: Spinopelvic dissociation represents a heterogeneous group of injuries often in the context of polytraumatized patients with other injuries. Our closed reduction and fixation technique resulted in satisfactory outcomes. We present a treatment algorithm for these rare injuries.